Buparlisib plus carboplatin or lomustine in patients with recurrent glioblastoma: a phase Ib/II, open-label, multicentre, randomised study. Issue 4 (13th July 2020) - Rosenthal, Mark; Clement, Paul M; Campone, Mario; Gil-Gil, Miguel J; DeGroot, John; Chinot, Olivier; Idbaih, Ahmed; Gan, Hui; Raizer, Jeffrey; Wen, Patrick Yung; Pineda, Estela; Donnet, Valerie; et al.
Abstract : Background: Glioblastoma relapse is associated with activation of phosphatidylinositol 3-kinase (PI3K) signalling pathway. In preclinical studies, the pan-PI3K inhibitor buparlisib showed antitumour activity in glioma models. Methods: This was a two-part, multicentre, phase Ib/II study in patients with recurrent glioblastoma pretreated with radiotherapy and temozolomide standard of care. Patients received buparlisib (80 mg or 100 mg once daily) plus carboplatin (area under the curve (AUC)=5 every 3 weeks), or buparlisib (60 mg once daily) plus lomustine (100 mg/m 2 every 6 weeks). The primary endpoint was to determine the maximum tolerable dose (MTD) and/or recommended phase II dose of buparlisib plus carboplatin or lomustine. Results: Between 28 February 2014 and 7 July 2016, 35 patients were enrolled and treated with buparlisib plus carboplatin (n=17; buparlisib (80 mg) plus carboplatin, n=3; and buparlisib (100 mg) plus carboplatin, n=14), or buparlisib (60 mg) plus lomustine (n=18). The MTD of buparlisib was determined to be 100 mg per day in combination with carboplatin at an AUC of 5 every 3 weeks. The MTD of buparlisib in combination with lomustine could not be determined as it did not satisfy the MTD criteria per the Bayesian logistic regression model. Conclusion: The overall safety profile of buparlisib remained unchanged, and no new or unexpected safety findings were reported in this study. Preliminary assessment for both combinations did not demonstrate sufficient antitumour activity compared with historical data on single-agent carboplatin or lomustine. Trial registration number: NCT01934361 .